Native Witchcraft Beliefs in Acadian, Maritime and Newfoundland Folklore - Labelle, Ronald (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
Acadian traditional legends and beliefs have been collected and studied by various scholars, the foremost being Catherine Jolicoeur, who collected approximately 400 narratives dealing with the Aboriginal population of the Maritimes as part of her fieldwork in Acadian areas of New Brunswick. This article examines the issue of belief in Native witchcraft, not only in Acadian folklore, but also among anglophones of the Maritimes and Newfoundland, in order to point out similarities or differences in their traditional belief systems, and also in their attitudes towards Native groups. A comparison is made between the views held by Roman Catholic and Protestant groups, and particular attention is given to gender considerations regarding the identity of “witches,” drawing on sources ranging from the late seventeenth up to the twentieth century. The article demonstrates that during all periods of history since the first contacts between Europeans and the Aboriginal populations of the Atlantic Provinces, the former have viewed the latter as being potentially dangerous, and have suspected them of possessing malevolent supernatural powers.